Analysis of the best choice of franchise and start acquire new business in Colombia (2013)
Due to the importance of the Colombian economy businesses for their contribution to economic and social development of the country, and the need for more entrepreneurs to create business, in this study it will be analyzed the best choice between starting a new 3 business and acquire franchise plus the variables that must be considered for each option, since both are effective as long as you have the required entrepreneurial profile. Starting a new business is a challenge , because if you do not have an innovative idea or an existing business in the market but with an added value that allows you to have greater advantage over other businesses, you cannot stay for long, what is different from the franchise model that has a proven idea that works good, with an established recognition, goodwill and customers , who guarantee a return on investment much faster than starting a brand new business, as long as you have the qualities of a franchise entrepreneur.